2015
DOI: 10.1016/j.snb.2015.06.085
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cobinamide-based end-of-service-life indicator for detection of hydrogen cyanide gas

Abstract: We describe an inexpensive paper-based sensor for rapid detection of low concentrations (ppm) of hydrogen cyanide gas. A piece of filter paper pre-spotted with a dilute monocyanocobinamide [CN(H2O)Cbi] solution was placed on the end of a bifurcated optical fiber and the reflectance spectrum of the CN(H2O)Cbi was monitored during exposure to 1.0–10.0 ppm hydrogen cyanide gas. Formation of dicyanocobinamide yielded a peak at 583 nm with a simultaneous decrease in reflectance from 450–500 nm. Spectral changes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Glass fiber filter paper was used as the sensor medium; in previous studies, this specific type of paper demonstrated larger reflectance signals, presumably because it is thicker than traditional cellulose filter paper and allowed more light to reach the detector in the presented reflectance configuration [19]. Additionally, glass fiber filter paper is less affected by water vapors.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Glass fiber filter paper was used as the sensor medium; in previous studies, this specific type of paper demonstrated larger reflectance signals, presumably because it is thicker than traditional cellulose filter paper and allowed more light to reach the detector in the presented reflectance configuration [19]. Additionally, glass fiber filter paper is less affected by water vapors.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, glass fiber filter paper is less affected by water vapors. The concentration of Cbi concentration (50.0 ± 0.2 µM) was chosen to directly compare results with previously performed experiments of similar nature using HCN gas [19]. This Cbi concentration on paper was sufficient in detecting small changes in the Cbi reflectance spectrum; higher concentrations of Cbi on paper decreased the sensitivity to slight changes in H 2 S concentration upon exposure, where lower Cbi concentrations had undesirable signal-to-noise ratios.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations